Enhanced surface binding energy regulates uniform potassium deposition for stable potassium metal anodes. Issue 11 (5th March 2020) - Zhao, Xinxin; Chen, Fengjiao; Liu, Junqing; Cheng, Mingren; Su, Hai; Liu, Jianbo; Xu, Yunhua
Abstract : A SnO2 -coated carbon fiber mat is fabricated and used to guide uniform K nucleation/deposition for dendrite free K metal anodes. Abstract : Dendritic growth is a major obstacle for the development of potassium metal anodes in K-ion batteries, which causes low coulombic efficiency, poor cycling stability and safety hazards. Herein, we report a 3D SnO2 -coated conductive porous carbon nanofiber (PCNF) framework (PCNF@SnO2 ) as a host for K metal anodes. The SnO2 coating layer has a higher binding energy with K than with carbon and makes the PCNF framework highly potassiphilic, which regulates uniform K nucleation and deposition and suppresses dendritic growth. In addition, the interconnected 3D structure of the PCNF framework provides a large amount of void space and a robust structure to accommodate a large amount of K (87% @ 15 mg cm −2 ) and alleviate the stress/strain caused by volume expansion during plating/stripping. The PCNF@SnO2 –K composite anode demonstrates an ultralong cycling stability of 1700 h at 1 mA cm −2, which is superior to those of other K metal anodes and even comparable with those of Li metal anodes reported in the literature. More importantly, enhanced performance is also achieved in a full cell using the composite K metal anode. Our results highlight a promising strategy for the development of stable and safe K metal anodes in KIBs.